The Effect of Social Media, Brand Image and Products on Purchasing Decisions at the Mj Shop Manna Bengkulu Selatan Store - Rafika Afriyani; Ahmad Sholeh; Rahman Febliansa (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
The purpose of this study was to determine the effect of social media on purchasing decisions, the effect of brand image on purchasing decisions and the effect of products on purchasing decisions at the MJ Shop Manna Bengkulu Selatan store. This type of research uses quantitative research. The analytical method in this study uses multiple linear regression analysis, the coefficient of determination and hypothesis testing using the t test and f test. The number of samples studied was 100 respondents who bought goods at the MJ Shop Manna Shop, South Bengkulu. The results of the multiple linear regression analysis are Y = 5.045 + 0.375 X1 + 0.104 X2 + 0.430 X3, this illustrates a positive regression direction, meaning that social media variables (X1), brand image (X2) and products (X3) have a positive influence on Purchase decision (Y) at MJ SHOP, South Bengkulu Regency. The magnitude of the coefficient of determination from the calculation results using SPSS can be seen that the coefficient of determination from R square is 0.104. From the results of calculations using SPSS, it can be seen that the coefficient of determination of R square is 0.819. This means that the value of social media (X1) and the value of brand image (X2) and work facilities (X3) affect the purchase decision (Y) by 81.9% while the remaining 18.1% is influenced by other variables not examined in this study. . The results of the t test at a significance level of 0.05 explain that partially social media, brand image and products have a significant influence on purchasing decisions at MJ SHOP, South Bengkulu Regency.